The Effect of Service Quality on Customer Satisfaction at At the National Bank in Indonesia - Herwina, Yulia (International Journal of Entrepreneurship and Business Management, 2022)
Banks are financial institutions that serve as places to store funds from banks, government and private agencies, as well as individuals and carry out credit activities. Various services provided by banks are to serve financing needs and to launch a payment system mechanism for the economic sector. Service quality is one of the key factors for the success of a bank as a service company and it cannot be denied in today's business world, because there is nothing more important for a bank than overcoming the problem of customer satisfaction and satisfaction through service as one of its business commitments. The purpose of this study was to determine whether service quality affects customer satisfaction at a national bank in Indonesia. The number of samples in this study were 89 people. From the results of the overall validity test of statement items between the service quality variable and the satisfaction variable it is declared valid because the value of rcount > rtable. The simple linear regression results show that the service quality variable has a significant effect on the satisfaction variable.